PERTANGGUNGJAWABAN RUMAH SAKIT TERHADAP MALPRAKTIK YANG DILAKUKAN TENAGA MEDIS DALAM PERSFEKTIF HUKUM PERDATA - Roselyn Hutagaol; Dhaniswara K. Harjono; Hulman Panjaitan (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
Hospital liability due to negligence or carelessness or in the event of malpractice by medical personnel from a civil perspective really depends on the pattern of legal relations between medical personnel and the hospital, whether the pattern of legal relations is based on employment law relations or legal relations. This really determines the extent to which a hospital can offer medical personnel actions that result in harm to patients in carrying out health services as part of their professional duties. Based on this legal relationship pattern, the hospital's liability can be based on unlawful acts as regulated in Article 1367 at (3) of the Civil Code and/or will be free from liability if the hospital can prove that the relationship pattern of medical personnel with the hospital is based on a lease.